Filtração de partículas através do dossel de uma floresta tropical úmida - MacInnis, Gail; Greene, David; Straka, Jason; Kevan, Peter (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
Understanding the dinamics of filtration of pollen and spores by plant canopies is crucial to the in the modelling of their dispersal, yet few studies have quantified filtration. Here, we examine the decline in the density of flour particles descending through a 40 m-tall tropical canopy on a windless day at Caxiuanã National Forest, Pará, Brazil. Using these data and estimates of canopy leaf density, we also tested one of the few existing models for the effect of impaction. The Bache model, which incorporates particle and vegetation structure, probability of particle transmission and the probability of impaction, explained approximately 93% of the variation in flour granules captured on passive samplers placed throughout the canopy. The canopy filtered 99.65% of the flour released, but a significant amount of small particles were captured at the forest floor. These findings suggest that the rarity of anemophily seen in the tropics may be more a result of high species richness than high canopy density.